The first four years - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York, NY : HarperTrophy, 1971)
During their first four years of marriage, Laura and Almanzo Wilder have a child and fight a losing battle in their attempts to succeed at farming on the South Dakota prairie.
Keywords: Frontier and pioneer life -- Fiction; South Dakota -- Fiction